Behavioral and Molecular Responses to Exogenous Cannabinoids During Pentylenetetrazol-Induced Convulsions in Male and Female Rats - Zirotti Rosenberg, Antonella; Méndez-Ruette, Maxs; Gorziglia, Mario; Alzerreca, Benjamín; Cabello, Javiera; Kaufmann, Sofía; Rambousek, Lukas; Iturriaga Jofré, Andrés; Wyneken, Ursula; Lafourcade, Carlos A. (Frontiers in Molecular Neuroscience, 2022)
Epilepsy is a disabling, chronic brain disease,affecting ~1% of the World’s population, characterized by recurrent seizures (sudden, uncontrolled brain activity), which may manifest with motor symptoms (e.g., convulsions) or non-motor symptoms. Temporal lobe epilepsies (TLE) compromising the hippocampus are the most common form of focal epilepsies. Resistance in ~1/3 of epileptic patients to the first line of treatment, i.e., antiepileptic drugs (AEDs), has been an important motivation to seek alternative treatments. Among these, the plant Cannabis sativa (commonly known as marihuana) or compounds extracted from it (cannabinoids) have gained widespread popularity. Moreover, sex differences have been proposed in epilepsy syndromes and in cannabinoid action. In the hippocampus, cannabinoids interact with the CB1R receptor whose membrane levels are regulated by β-Arrestin2, a protein that promotes its endocytosis and causes its downregulation. In this article, we evaluate the modulatory role of WIN 55,212-2 (WIN), a synthetic exogenous cannabinoid on behavioral convulsions and on the levels of CB1R and β-Arrestin2 in female and male adolescent rats after a single injection of the proconvulsant pentylenetetrazol (PTZ). As epilepsies can have a considerable impact on synaptic proteins that regulate neuronal toxicity, plasticity, and cognition, we also measured the levels of key proteins markers of excitatory synapses, in order to examine whether exogenous cannabinoids may prevent such pathologic changes after acute seizures. We found that the exogenous administration of WIN prevented convulsions of medium severity in females and males and increased the levels of phosphorylated CaMKII in the hippocampus. Furthermore, we observed a higher degree of colocalization between CB1R and β-Arrestin2 in the granule cell layer.